Characteristics of knowledge translation platforms and methods for evaluating them: a scoping review protocol - Taryn Young; Bey-Marrié Schmidt; Sara Cooper; Nasreen S Jessani (BMJ Open)
Introduction Knowledge translation platforms (KTPs) are intermediary organisations, initiatives or networks whose intent is to bridge the evidence into action divide. Strategies and tools include collaborative knowledge production, capacity building, information exchange and dialogue to facilitate relevant and timely engagement between researchers and decision-makers and other relevant stakeholders. With the wide range of definitions and descriptions of KTPs, there is a need to (1) provide a nuanced understanding of characteristics of KTPs and (2) assess and consolidate research methods used in mapping and evaluating KTPs to inform standardised process and impact evaluation.Methods and analysis This scoping review will follow the recommended and accepted methods for scoping reviews and reporting guidelines. Eligibility for inclusion is any conceptual or empirical health-related qualitative, quantitative and/or mixed method studies including (1) definitions, descriptions and models or frameworks of KTPs (including those that do not self-identify as KTPs, eg, university research centres) and (2) research methods for mapping and/or evaluating KTPs. Searches will be carried out in PubMed, Scopus, CINAHL, Embase, Global Health and Web of Science using a predetermined search strategy, without any date, language or geographical restrictions. Two reviewers will independently screen titles and abstracts. One reviewer will complete data extraction for all included studies, and another will check a sample of 50% of the included studies. The analysis and synthesis will provide (1) an understanding of the various characteristics of KTPs; (2) insight into characteristics or factors that make them resilient and/or adaptive to facilitate impact (ie, influence policy and practice); and (3) an overview of the various methods for mapping and evaluating KTPs. We will explore enhancing an existing framework for classifying KTPs, or perhaps even developing a new framework for identifying and monitoring KTPs if necessary and relevant.Ethics and dissemination This scoping review does not require ethics approval, as we will only include information from previously conducted studies and we will not involve human participants. The results will be submitted to a peer-reviewed scientific journal for publication and as conference presentations.